Unveiling the dynamics of sustainable financial markets: The role of issuer commitment, third-party verification, and regulation in the ESG alignment of green bonds - Dewi Cahyani Pangestuti (Jurnalku, 2026)
Over the past decade, green bonds have emerged as a central instrument in sustainable finance markets, functioning as a strategic mechanism for advancing Environmental, Social, and Governance (ESG) objectives. However, their effective alignment with ESG goals remains constrained by regulatory heterogeneity, divergent investment criteria, and variations in the credibility of third-party verification systems. This study aims to identify the key determinants shaping the ESG alignment of green bonds and to comparatively evaluate their effectiveness relative to other sustainable financial instruments, particularly sustainability-linked bonds (SLBs) and social bonds. This research adopts a systematic literature review methodology based on Scopus-indexed publications from 2019 to 2025, applying thematic synthesis and comparative analysis across regions, regulatory contexts, and methodological approaches. The findings indicate that issuer sustainability commitment and credible third-party verification constitute the primary determinants of green bond credibility and pricing, as reflected in the yield discount phenomenon known as the greenium. Moreover, green bonds tend to prioritize the environmental dimension of ESG, whereas SLBs introduce more flexible, performance-based incentive mechanisms. Advanced regulatory frameworks and coherent sustainability taxonomies are shown to play a critical role in accelerating market maturity, strengthening investor confidence, and enhancing market scalability. The study underscores the importance of integrating issuer commitment, independent verification, and coordinated regulatory structures to reinforce the credibility, effectiveness, and long-term scalability of green bond markets in supporting the achievement of global ESG objectives.